An application framework for managing knowledge in open source software development - Abdullah, Rusli; Lukulu, Modi; Ibrahim, Hamidah; Selamat, Mohd Hasan (2013)
The present invention relates to an application framework (100) for managing knowledge in open source software development characterized by: domain open source knowledge (101) comprising an open source software development process; knowledge management process (102) for acquiring, collecting, organizing, disseminating or sharing the domain open source knowledge (101); repository (103) for storing the domain open source knowledge (101); community of practice (104) in the open source software development; networking system (105) for supporting communication among the community of practice (104); and connection platform (106) for connecting the community of practice (104) to the repository (103) and networking system (105).